HARMONI DALAM BAYANG MINORITAS: DINAMIKA IDENTITAS KEAGAMAAN MUSLIM SINGAPURA - Afwaz Fafaza Rif'ah; Abu Haif; Sattu Alang (Yayasan Haiah Nusratul Islam, 2026)
This article aims to examine the religious identity of the minority Muslim community in Singapore, a secular, multi-religious state with a Muslim population of approximately 15% (most of whom are Malay). Once the center of Islam in Southeast Asia during the Malacca Sultanate, Singapore has developed into a developed nation following its independence from the Malaysian federation in 1965. Despite its perceived neutrality towards various religions, the government has implemented policies that limit the spread of Islam, such as a ban on loud calls to prayer, the use of headscarves in public schools and government institutions, and a restructuring of propaganda that impacts the homogenous Muslim community. The goal is to maintain social harmony across ethnicities (with a Chinese majority) and religions (Buddhists 33%, Christians 18%). To adapt, Muslims formed organizations such as the independent but government-recognized Islamic Religious Council of Singapore (MUIS), which manages fatwas, hajj, zakat, waqf (endowments), mosques (70 units), and madrasas. MUIS also ensures that religious sermons are conducted with tolerance and inclusivity, which includes monitoring foreign preachers. In addition to MUIS, PERGAS and PERDAUS exist, which focus on Islamic education. Overall, the minority Muslim community in Singapore demonstrates the resilience of its identity by adapting to secularism, while contributing to national diversity, despite limitations to prevent potential radicalization. This document emphasizes the importance of religion in both the private and public spheres, referencing international minority rights treaties such as the ICCPR.